The effect of biosurfactant in solving of petrochemical industry wastewater treatment - Pettrus, Akun (2006)
A research has been conducted to study the effect of biosurfactant in solving of petrochemical industry wastewater treatment. Biosurfactant is an alternative method to industrial wastewater treatment nowadays. Biosurfactant has the ability to treat wastewater by using naturally- occurring micro organisms to breakdown or to degrade hazardous substances into less or non toxic materials. Technologies using microorganisms and microbial products to remove metals have been successfully applied to waste streams. Metals that are widely concerned in waste treatment are mercury. In this study, biosurfactant is applied to wastewater to treat the mercury in the wastewater. Using current wastewater treatment pilot plant and HACH wastewater quality equipment technology in this project helps improve the progress of the research. Besides focusing onto mercury treatment, an observation to the values of BOD, COD and pH also will be made. Basically, the result obtained from the project will demonstrate that biosurfactant can be applied as one of the method to study the petrochemical wastewater treatment.